#StayHomeStayFit: UNIMI’s approach to online healthy lifestyle promotion during the COVID-19 pandemic.: Running Title: #StayHomeStayFit: COVID-19 health bits - Lucini, Daniela; Gandolfi, Cecilia Eugenia; Antonucci, Clara; Cavagna, Anna; Valzano, Esther; Botta, Elena; Chiari, Matteo; Mameli, Lorenzo; Nahum, Margherita; Brambilla, Marina Marzia; Castaldi, SIlvana; Biganzoli, Elia (Acta Biomedica Atenei Parmensis, 2020)
ABSTRACT The COVID-19 lockdown imposed radical changes in the lifestyles of the population through isolation measures, with considerable health, social, psychological and economic consequences. Lockdown measures may have exacerbated negative population behaviors regarding exercise and nutrition, with risk of weight gain and obesity, collectively predisposing to increased cardiometabolic risk and mortality. At particular risk of deleterious consequences were patients such as those affected by chronic non communicable diseases (CNCD). The benefits of regular exercise are evident at several levels of CNCD prevention, however, from a public health standpoint, it is important to consider they are also related to improved stress management, work/academic performance, and reduced illegal behavior, isolation and depression. Therefore, during enforced isolation, a primary goal for all individuals is to maintain energy balance. During lockdown, several lifestyle interventions were posted online, with the internet playing a major role in exercise and fitness promotion. Among these one must recognize the ambitious “#StayHomeStayFit” project by the University of Milan, providing useful general information and trustworthy advice regarding nutrition, physical activity, and psychological support, for the general population in a time of need. Data showed a total of 21224 views on various social media and webpages during the reference period, with a mean time of 4’ 17’’ spent per page/video. Given the health risks associated with population physical inactivity and unhealthy lifestyle, policymakers should evaluate the benefits of projects such as #StayHomeStayFit and consider how to maximize population perception and reach. After all, additional COVID-19 lockdowns might be implemented in the future.